1995
DOI: 10.1159/000139364
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Antilipolytic Effects of the Adenosine Agonist GR79236

Abstract: Adenosine is known to produce cardiovascular effects such as bradycardia and hypotension via activation of myocardial (A1) and vascular (A2) receptors and antilipolytic effects through activation of adipocyte (A1) receptors. We established the cardiovascular and antilipolytic profile of the adenosine A1 agonist GR79236 (N6-[(lS, trans)-2-hydroxycyclopentyl]-adenosine) and compared it with CPA (N6-cyclopentyl-adenosine). GR79236 was approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
5
24
0
Order By: Relevance
“…Moreover, the close correlation between inhibition of lipolysis in rat and human adipocytes found for both AMP 579 and CPA is in agreement with data reported on the A 1 selective agonist GR 79236 in rat and human adipocytes Heseltine et al, 1995). The ability of adenosine agonists to inhibit lipolysis in vitro has long been known and has been described for various N 6 -substituted adenosine A 1 -selective agonists, including R-PIA (Fredholm, 1978), BM11.189 (Wieser and Pendleton, 1979), GR 79236 Merkel et al, 1995), and SDZ-WAG 994 (Deems et al, 1994). Nonselective adenosine A 1 /A 2 agonists, such as NECA (Fredholm, 1978;Gurden et al, 1993), and A 2A -selective agonists, such as CGS21680 and CV1808 , have also been evaluated and their order of potency confirmed that inhibition of lipolysis is indeed an A 1 -mediated event.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the close correlation between inhibition of lipolysis in rat and human adipocytes found for both AMP 579 and CPA is in agreement with data reported on the A 1 selective agonist GR 79236 in rat and human adipocytes Heseltine et al, 1995). The ability of adenosine agonists to inhibit lipolysis in vitro has long been known and has been described for various N 6 -substituted adenosine A 1 -selective agonists, including R-PIA (Fredholm, 1978), BM11.189 (Wieser and Pendleton, 1979), GR 79236 Merkel et al, 1995), and SDZ-WAG 994 (Deems et al, 1994). Nonselective adenosine A 1 /A 2 agonists, such as NECA (Fredholm, 1978;Gurden et al, 1993), and A 2A -selective agonists, such as CGS21680 and CV1808 , have also been evaluated and their order of potency confirmed that inhibition of lipolysis is indeed an A 1 -mediated event.…”
Section: Discussionsupporting
confidence: 87%
“…Although it has been long known that A 1 agonists are potent and efficacious inhibitors of lipolysis, limited efforts have been directed at the development of A 1 agonists as potential therapeutic antilipolytic agents, mainly due to the potential for adverse cardiovascular effects. Previous work with GR79236, an A 1 agonist, revealed that with this agonist it was not possible to obtain a substantial separation between its lipid-lowering and cardiovascular effects (Merkel et al, 1995). With CVT-510, NEFA levels can be lowered by approximately 60 to 70% at doses that this agonist does not cause bradycardia, whereas with GR79236, at concentrations that reduced glycerol 60%, heart rate was lowered approximately 30% (Merkel et al, 1995).…”
Section: Antilipolytic Effect Of Cvt-510 Without Bradycardia 229mentioning
confidence: 99%
“…Previous work with GR79236, an A 1 agonist, revealed that with this agonist it was not possible to obtain a substantial separation between its lipid-lowering and cardiovascular effects (Merkel et al, 1995). With CVT-510, NEFA levels can be lowered by approximately 60 to 70% at doses that this agonist does not cause bradycardia, whereas with GR79236, at concentrations that reduced glycerol 60%, heart rate was lowered approximately 30% (Merkel et al, 1995). Work by van Schaick et al (1997) on the other hand, with N-6-(p-sulfophenyl) adenosine did show some tissue selectivity in vivo (van Schaick et al, 1997).…”
Section: Antilipolytic Effect Of Cvt-510 Without Bradycardia 229mentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction of lipolysis in adipocytes is of potential benefit in treatments of dyslipidemia, type II diabetes, and metabolic syndrome (Bergman et al, 2001;Boden and Laakso, 2004;DeFronzo, 2004;Lebovitz and Banerji, 2004). However, A 1 AdoR agonists have potential unintended side effects as a result of the presence of A 1 AdoR in many other tissues (Merkel et al, 1995).…”
mentioning
confidence: 99%